2016
DOI: 10.1097/dcr.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Optimal Timing for Initiation of Adjuvant Chemotherapy After Resection for Stage II and III Colon Cancer

Abstract: This study objectively determines the optimal timing of adjuvant chemotherapy for patients with resected colon cancer. Delay beyond 6 weeks is associated with compromised survival. These findings emphasize the importance of the timely initiation of therapy, and suggest that efforts to enhance recovery following surgery have the potential to improve survival by decreasing delay to adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 23 publications
1
45
0
1
Order By: Relevance
“…An encouraging finding of this study is that despite the higher R0 resection rate, an excellent 5-year overall survival rate of 67% was demonstrated in the neoadjuvant group. This is similar to the survival in the control group (65%) and comparable to recent literature [37][38][39]. Most importantly, these results are in accordance with the first results of the randomized phase FOxTROT trial that were presented at the ASCO annual meeting 2019.…”
Section: Discussionsupporting
confidence: 91%
“…An encouraging finding of this study is that despite the higher R0 resection rate, an excellent 5-year overall survival rate of 67% was demonstrated in the neoadjuvant group. This is similar to the survival in the control group (65%) and comparable to recent literature [37][38][39]. Most importantly, these results are in accordance with the first results of the randomized phase FOxTROT trial that were presented at the ASCO annual meeting 2019.…”
Section: Discussionsupporting
confidence: 91%
“…Time cutoffs defining a delay in adjuvant chemotherapy initiation have varied from one month to three months in previous studies [ 5 - 19 ], and a time delay in chemotherapy has been reported to adversely influence [ 5 , 7 , 10 , 11 , 14 - 17 , 19 ] or not influence the oncologic outcome (Table 1 ) [ 6 , 8 , 9 , 12 , 13 , 18 ]. It is still controversial whether a delay in chemotherapy negatively influences oncologic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Smooth transition to postoperative adjuvant chemotherapy is critical in colorectal cancer treatment. Although currently there is no consensus on the exact time to initiate adjuvant chemotherapy, it is generally agreed that the start time of chemotherapy should be no later than 8 weeks after operation [5][6][7][8][9]. The potential reasons for the delay of chemotherapy generally lie in the following aspects: patient-related factors such as lower socioeconomic status, female gender, and older age; treatmentrelated factors such as postoperative complications, surgical approach (open vs laparoscopic), and chemotherapy reagents; social and psychological factors such as lack of insurance, lack of social support, and insufficient knowledge on chemotherapy [10,[19][20][21][22].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…A systematic and meta-analysis involving 15,410 colorectal patients demonstrated that a 4-week increment in time to adjuvant chemotherapy was associated with a 14% decrease in both overall survival (OS) and disease-free survival (DFS) [6]. Another two large-scale retrospective studies from the US and Netherlands National Cancer Database also showed that a delay of 6-8 weeks between surgery and adjuvant therapy would reduce survival in stage II and III colorectal cancer patients [7,8].…”
Section: Introductionmentioning
confidence: 99%